Modeling Hyperglycemia With Induction Variants In Mice As Preclinical Test Animals - Santoso, Setiyo B.; Hapsari, Widarika S.; Putra, Deksa Y.S (Pharmacology and Clinical Pharmacy Research, 2024)
Inducing hyperglycemia in animal models is crucial for preclinical research on anti-diabetic drug development, especially when genetically diabetic test animals are unavailable. Various induction methods have been employed to elevate glycemic levels in test animals. However, there is a lack of substantial literature proving the effectiveness and stability of these induction alternatives. This study aims to compare the stability of glycemic levels and assess histopathological changes in mice induced by dextrose, streptozotocin, and alloxan. Our protocol involved dividing mice into six groups of five, each with a control group. Mice in Groups A and D were exposed to alloxan monohydrate, Groups B and E to streptozotocin, and Groups C and F to dextrose monohydrate, inducing hyperglycemia for nine days following a seven-day acclimatization period. Pancreatic histopathology examination included features such as cytoplasmic vacuolization, fat infiltration, and islet deformation. The study revealed that, compared to dextrose and streptozocin, alloxan demonstrated superior efficacy in inducing and maintaining hyperglycemic stability in mice. However, the histopathological assessment of the pancreas indicated the relatively benign nature of dextrose monohydrate and streptozotocin, with no apparent exacerbation of pancreatic impairment. In contrast, alloxan induced evident islet deformation and cytoplasmic vacuolization. Our findings suggest that, in comparison to alloxan, dextrose monohydrate and streptozotocin are more favorable for inducing hyperglycemia in test animals. They pose a lower risk of significant pancreatic impairment, indicating their potential suitability for modeling type 2 diabetes mellitus due to their stability and relatively benign impact on pancreatic histopathology.